2003
DOI: 10.1104/pp.103.021758
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Two Arabidopsis Type III Phosphatidylinositol 4-Kinase Isoforms. A Regulatory Role for the Pleckstrin Homology Domain

Abstract: Here, we compare the regulation and localization of the Arabidopsis type III phosphatidylinositol (PtdIns) 4-kinases, AtPI4K␣1 and AtPI4K␤1, in Spodoptera frugiperda (Sf9) insect cells. We also explore the role of the pleckstrin homology (PH) domain in regulating AtPI4K␣1. Recombinant kinase activity was found to be differentially sensitive to PtdIns-4-phosphate (PtdIns4P), the product of the reaction. The specific activity of AtPI4K␣1 was inhibited 70% by 0.5 mm PtdIns4P. The effect of PtdIns4P was not simply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
3
30
1
1
Order By: Relevance
“…Phosphorylation of PI in chloroplasts was reported to be sensitive to WM (Bovet et al, 2001), which was consistent with a previous study showing that PI4Ka1 was inhibited by WM (Stevenson-Paulik et al, 2003). Although we demonstrated the relationship between PI4Ka1 and chloroplast division, the functions of PI4Ka1 have not been thoroughly studied because null mutations of the PI4Ka1 gene are lethal (Delage et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Phosphorylation of PI in chloroplasts was reported to be sensitive to WM (Bovet et al, 2001), which was consistent with a previous study showing that PI4Ka1 was inhibited by WM (Stevenson-Paulik et al, 2003). Although we demonstrated the relationship between PI4Ka1 and chloroplast division, the functions of PI4Ka1 have not been thoroughly studied because null mutations of the PI4Ka1 gene are lethal (Delage et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…This suggests that SAtriggered PI 4-kinase is located close to the site of PI synthesis, most probably on the endoplasmic reticulum (Sandelius and Morré, 1987). Interestingly, Arabidopsis PI 4-kinase a1 fused with GFP was visualized in endoplasmic reticulum membranes at the perinuclear region in insect cells (Stevenson-Paulik et al, 2003).…”
Section: Activation Of a Pi 4-kinase As An Early Response To Samentioning
confidence: 94%
“…One straightforward explanation for this striking difference in WM sensitivity is based on our observation that the CSD suppresses lateral diffusion and separates the two polar domains. It has repeatedly been reported that WM affects internalization of proteins from the PM, which might be independent-or an indirect consequence-of its action on the endosomal PI-3 kinase (28)(29)(30). Lower WM concentrations expectedly induced accumulation of BOR1 and NIP5;1 in aberrant endosomes, revealing that a certain fraction of both proteins became endocytosed and trapped in these compartments.…”
Section: The Polarity Realized In the Endodermis Is Established Earlymentioning
confidence: 99%